LEVEL-BASED CORRESPONDENCE APPROACH TO COMPUTATIONAL STEREO - MAHABADI, SEYED ALI KASAEIZADEH MAHABADI (2010)
One fundamental problem in computational stereo reconstruction is correspondence. Correspondence is the method of detecting the real world object reflections in two camera views. This research focuses on correspondence, proposing an algorithm to improve such detection for low quality cameras (webcams) while trying to achieve real-time image processing. Correspondence plays an important role in computational stereo reconstruction and it has a vast spectrum of applicability. This method is useful in other areas such as structure from motion reconstruction, object detection, tracking in robot vision and virtual reality. Due to its importance, a correspondence method needs to be accurate enough to meet the requirement of such fields but it should be less costly and easy to use and configure, to be accessible by everyone. By comparing current local correspondence method and discussing their weakness and strength, this research tries to enhance an algorithm to improve previous works to achieve fast detection, less costly and acceptable accuracy to meet the requirement of reconstruction. In this research, the correspondence is divided into four stages. Two stages of preprocessing which are noise reduction and edge detection have been compared with respect to different methods available. In the next stage, the feature detection process is introduced and discussed focusing on possible solutions to reduce errors created by system or problem occurring in the scene such as occlusion. Lastly, in the final stage it elaborates different methods of displaying reconstructed result. Different sets of data are processed based on the steps involved in correspondence and the results are discussed and compared in detail. The finding shows how this system can achieve high speed and acceptable outcome despite of poor quality input. As a conclusion, some possible improvements are proposed based on ultimate outcome.